Becoming a “Better” Father: Supporting the Needs of Incarcerated Fathers - Fowler, Cathrine (The prison journal, 2017)
Given the importance of fathering to the well-being and development of children, paternal incarceration has a major impact on children and families. Drawing on interviews with 64 incarcerated fathers in New South Wales, Australia, this article explores their experiences. The men’s childhood familial separation and disconnection is frequently repeated in adulthood, with limited contact with their own families even when not in custody. Despite barriers to connection, the interviewees express strong aspirations to be “good” fathers and to achieve a “better life” for their children. The absence of stable models of responsive fathering in early life is a common theme that has implications for the development of education and support programs for imprisoned fathers.